Factors that Influence the Provision of Breastfeeding - Teta Puji Rahayu; Ayesha Hendriana Ngestiningrum (Humanistic Network for Science and Technology (HNST), 2019)
Exclusive breastfeeding is one form of health behavior that provides great benefits to babies, mothers and the state. The purpose of the study analyzed the relationship between age, education, occupation, parity, mother attitude and husband support to exclusive breastfeeding. Type of cross-sectional study. The study sample of 88 mothers with infants aged 6-12 months in Magetan District, with cluster random sampling technique for the sub-district, while for kelurahan, posyandu, and respondents were taken by simple random sampling. Variables of age, education, occupation and parity were taken using questionnaires, maternal attitude variable and husband support were measured by Likert scale 1-5. Analysis was carried out using path analysis, with T value >1.96 and path coefficients